Method for verifying physical property and catalytic performance of aluminum, gallium and zinc doped modified copper oxide
By doping aluminum, gallium and zinc in the Cu-based catalyst, the modified copper oxide nanoparticle catalyst was prepared, and the problems of low product selectivity, serious competitive hydrogen evolution reaction and poor stability during the carbon dioxide reduction process were solved, and an efficient and stable carbon dioxide reduction reaction was achieved.
Patent Information
- Application Number
- CN202510033412.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
During the carbon dioxide reduction process, the monometal Cu-based catalyst has low product selectivity, serious competitive hydrogen evolution reaction and poor stability.
By doping aluminum, gallium, and zinc in Cu-based catalysts, a modified copper oxide nanoparticle catalysts are prepared, and a gas diffusion electrode is prepared by ball milling and ultrasonic vibration to verify its physical properties and catalytic properties.
The selectivity and stability of the carbon dioxide reduction reaction are significantly improved, the adsorption strength of the reactive oxygen components on the copper surface is enhanced, the Faraday efficiency of electrocatalytic carbon dioxide reduction is higher, and the C2+ Faraday efficiency reaches 90%.
Smart Images

Figure CN119804812A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and in particular relates to a method for verifying the physical properties and catalytic performance of aluminum-, gallium- and zinc-doped modified copper oxide. Background Art
[0002] Traditional fossil fuels, such as coal, oil and natural gas, are the driving force for the development of modern society. Due to the limited reserves of fossil resources, their exploitation efforts are still gradually increasing, which faces a serious problem of resource depletion. Using fossil fuels as energy suppliers has also led to a sharp increase in carbon dioxide emissions. Excessive concentrations of carbon dioxide in the atmosphere will cause many environmental problems, such as global warming, land desertification, and seawater acidification. Therefore, mitigating carbon dioxide emissions is a very urgent issue. Using clean electricity generated by renewable energy such as solar energy and wind energy to catalyze carbon dioxide reduction reactions to prepare high-value-added chemical raw materials and fuels can not only reduce carbon emissions, but also effectively alleviate the energy crisis. Cu is a catalyst that can effectively promote the reduction of carbon dioxide to multi-carbon products, but the Cu catalytic reaction mechanism is relatively complex, the products are complex, and competitive hydrogen evolution reactions are prone to occur, resulting in low electrocatalytic conversion efficiency. Therefore, inhibiting the hydrogen evolution reaction is the key to improving the efficiency of carbon dioxide reduction to multi-carbon products.
[0003] Exploring economical, high-efficiency, and stable catalytic electrode materials is crucial to improving conversion efficiency and inhibiting hydrogen evolution reaction. Doping metal elements on Cu-based catalysts is a way to adjust the binding strength of intermediates and thus improve CO2-to-C 2+ Therefore, the cation-doped CuO catalyst can effectively inhibit the hydrogen evolution reaction, improve the reaction selectivity, and promote the stability of carbon dioxide reduction. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for verifying the physical properties and catalytic performance of aluminum, gallium and zinc doped modified copper oxide, which aims to solve the problems of low selectivity of carbon dioxide reduction products, serious competitive hydrogen evolution reaction and poor stability of single metal Cu-based catalysts.
[0005] The technical solution adopted by the present invention is: a method for verifying the physical properties and catalytic performance of aluminum, gallium and zinc doped modified copper oxide, the method comprising the following steps: Step 1: Preparation of aluminum, gallium, and zinc doped modified copper oxide nanoparticles catalyst 1.5 g of copper oxide nanoparticle powder, 1.5 g of aluminum salt and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The ball-milled mixture was taken out, centrifuged and washed to remove impurities, and then the centrifuged mixture was freeze-dried to obtain aluminum-doped modified copper oxide nanoparticle catalyst powder.
[0006] 1.5 g of copper oxide nanoparticle powder, 1 g of gallium salt and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The ball-milled mixture was taken out, centrifuged and washed to remove impurities, and then the centrifuged mixture was freeze-dried to obtain gallium-doped modified copper oxide nanoparticle catalyst powder.
[0007] 1.5 g of copper oxide nanoparticle powder, 1.2 g of zinc salt, and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The mixture after ball milling was taken out, centrifuged and washed to remove impurities, and then the mixture after centrifugation was freeze-dried to obtain zinc-doped modified copper oxide nanoparticle catalyst powder.
[0008] Step 2: Preparation of gas diffusion electrode of aluminum, gallium and zinc doped modified copper oxide nanoparticle catalyst The aluminum-doped modified copper oxide nanoparticle catalyst prepared in step 1 and Nafion ( Perfluorosulfonic acid type polymerization solution ) was ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain aluminum-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of aluminum-doped modified copper oxide nanoparticle catalyst.
[0009] The gallium-doped modified copper oxide nanoparticle catalyst prepared in step 1 and Nafion ( Perfluorosulfonic acid type polymerization solution ) was ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain gallium-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of gallium-doped modified copper oxide nanoparticle catalyst.
[0010] The zinc-doped modified copper oxide nanoparticle catalyst prepared in step 1 and Nafion ( Perfluorosulfonic acid type polymerization solution ) was ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain zinc-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of zinc-doped modified copper oxide nanoparticle catalyst.
[0011] Step 3: Verify the physical properties of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts The physical properties of aluminum-doped modified copper oxide nanoparticle catalyst, gallium-doped modified copper oxide nanoparticle catalyst and zinc-doped modified copper oxide nanoparticle catalyst samples were characterized by X-ray diffraction and scanning electron microscopy, respectively.
[0012] Step 4: Verify the catalytic performance of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts Electron microscope scanning was performed on aluminum-, gallium- and zinc-doped modified copper oxide nanoparticle catalysts respectively, and the structures of aluminum-doped modified copper oxide nanoparticles, gallium-doped modified copper oxide nanoparticles and zinc-doped modified copper oxide nanoparticles were analyzed through scanning photos.
[0013] In a flow cell system, the electrocatalytic carbon dioxide reduction activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified respectively. The gas diffusion electrode loaded with aluminum, gallium, and zinc doped modified copper oxide nanoparticles was used as the cathode, the iridium mesh was used as the anode, the Hg / HgO electrode was used as the reference electrode, and the electrolyte was 1 mol / L KOH; and the catalytic activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified by Faraday efficiency diagrams.
[0014] Beneficial effects of the invention: The invention provides a method for verifying the physical properties and catalytic performance of aluminum, gallium, and zinc doped modified copper oxide. The purpose is to solve the problems of low selectivity of carbon dioxide reduction products, severe competitive hydrogen evolution reaction, and poor stability of single metal Cu-based catalysts. It has been verified that the catalyst of aluminum-doped modified copper oxide nanoparticles has higher electrocatalytic carbon dioxide reduction reaction activity, can significantly enhance the adsorption strength of active oxygen components on the copper surface and stabilize key intermediates, thereby improving product selectivity; stable performance, high Faraday efficiency of electrocatalytic carbon dioxide reduction, FE C2+ The verification method and preparation process are simple and easy to promote and apply on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the X-ray diffraction pattern of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalyst; Figure 2 is the SEM image of aluminum-doped modified copper oxide nanoparticles; Figure 3 is the SEM image of gallium-doped modified copper oxide nanoparticles; Figure 4 is the SEM image of zinc-doped modified copper oxide nanoparticles; Figure 5 is the EDS image of aluminum-doped modified copper oxide nanoparticles; Figure 6 is the EDS image of gallium-doped modified copper oxide nanoparticles; Figure 7 is the EDS image of zinc-doped modified copper oxide nanoparticles; Figure 8 This is the Faraday efficiency diagram of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts in electrochemical performance tests; DETAILED DESCRIPTION Example
[0016] A method for verifying the physical properties and catalytic performance of aluminum, gallium and zinc doped modified copper oxide, the method comprising the following steps: Step 1: Preparation of aluminum, gallium, and zinc doped modified copper oxide nanoparticles catalyst 1.5 g of copper oxide nanoparticle powder, 1.5 g of aluminum salt and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The ball-milled mixture was taken out, centrifuged and washed to remove impurities, and then the centrifuged mixture was freeze-dried to obtain aluminum-doped modified copper oxide nanoparticle catalyst powder.
[0017] 1.5 g of copper oxide nanoparticle powder, 1 g of gallium salt and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The ball-milled mixture was taken out, centrifuged and washed to remove impurities, and then the centrifuged mixture was freeze-dried to obtain gallium-doped modified copper oxide nanoparticle catalyst powder.
[0018] 1.5 g of copper oxide nanoparticle powder, 1.2 g of zinc salt, and 1.5 g of urea were put into a ball mill and ball-milled in a ball mill. The mixture after ball milling was taken out, centrifuged and washed to remove impurities, and then the mixture after centrifugation was freeze-dried to obtain zinc-doped modified copper oxide nanoparticle catalyst powder.
[0019] Step 2: Preparation of gas diffusion electrode of aluminum, gallium and zinc doped modified copper oxide nanoparticle catalyst The aluminum-doped modified copper oxide nanoparticle catalyst prepared in step 1 and Nafion ( Perfluorosulfonic acid type polymerization solution ) was ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain aluminum-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of aluminum-doped modified copper oxide nanoparticle catalyst.
[0020] The gallium-doped modified copper oxide nanoparticle catalyst and Nafion prepared in step 1 were ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain gallium-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of gallium-doped modified copper oxide nanoparticle catalyst.
[0021] The zinc-doped modified copper oxide nanoparticle catalyst and Nafion prepared in step 1 were ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to obtain zinc-doped modified copper oxide nanoparticle catalyst ink, which was drop-coated on polytetrafluoroethylene (PTFE) hydrophobic carbon fiber paper to obtain a gas diffusion electrode of zinc-doped modified copper oxide nanoparticle catalyst.
[0022] Step 3: Verify the physical properties of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts The physical properties of aluminum-doped modified copper oxide nanoparticle catalyst, gallium-doped modified copper oxide nanoparticle catalyst and zinc-doped modified copper oxide nanoparticle catalyst samples were characterized by X-ray diffraction and scanning electron microscopy respectively; the X-ray diffraction patterns of aluminum-, gallium- and zinc-doped modified copper oxide nanoparticle catalysts are shown in Figure 1 As shown, the diffraction peaks of the prepared samples are consistent with the standard spectrum of CuO. In the case of different aluminum, gallium and zinc doped copper oxide, the crystal plane is consistent with the undoped counterpart. Different aluminum, gallium and zinc exist in the sample in the form of atomic doping.
[0023] Step 4: Verify the catalytic performance of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts Electron microscope scanning was performed on aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts, and the structures of aluminum doped modified copper oxide nanoparticles, gallium doped modified copper oxide nanoparticles, and zinc doped modified copper oxide nanoparticles were analyzed through scanning photos; the SEM structure comparison diagram of aluminum, gallium, and zinc doped modified copper oxide nanoparticles is shown in the figure. Figure 2 As shown in the figure, it can be determined from the analysis of the figure that the aluminum-doped modified copper oxide nanoparticles have an irregular nanoparticle structure; energy dispersive X-ray spectroscopy (EDS) is shown in Figure 3 As shown, aluminum, copper and oxygen elements are uniformly distributed in the aluminum-doped modified copper oxide nanoparticle catalyst.
[0024] In the flow cell system, the electrocatalytic carbon dioxide reduction activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified respectively. The gas diffusion electrode loaded with aluminum, gallium, and zinc doped modified copper oxide nanoparticles was used as the cathode, the iridium mesh was used as the anode, the Hg / HgO electrode was used as the reference electrode, and the electrolyte was 1 mol / L KOH; and the catalytic activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified by the Faraday efficiency diagram; the comparison of catalytic activity test results is shown in the figure below. Figure 4 As shown, the prepared aluminum, gallium, and zinc doped copper oxide nanoparticle catalyst has a C 2+ The Faraday efficiency is between 50% and 90%, among which the aluminum-doped modified copper oxide nanoparticle catalyst has the best effect. C2+ Reached 90%.
[0025] Studies have shown that the presence of monovalent copper is more conducive to the formation of carbon dioxide products than the presence of zero-valent copper and divalent copper. However, during the reduction of carbon dioxide, due to the high negative potential, monovalent copper is continuously reduced to zero-valent copper, resulting in catalyst deactivation. Therefore, stabilizing the monovalent copper sites in the catalyst is crucial for the efficient generation of carbon dioxide products. Aluminum doping into copper oxide can adjust the electronic structure around the catalyst and is beneficial to the electrocatalytic activity. As a Lewis acid center, aluminum doping can stabilize the monovalent copper component, enhance the adsorption of active oxygen species and inhibit the breakage of C−O bonds to facilitate the formation of carbon dioxide products.
[0026] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for verifying the physical properties and catalytic performance of aluminum, gallium and zinc doped modified copper oxide, characterized in that: The method comprises the following steps: Step 1: Preparation of aluminum, gallium, and zinc doped modified copper oxide nanoparticles catalyst 1.5 g of copper oxide nanoparticle powder, 1.5 g of aluminum salt and 1.5 g of urea were put into a ball milling jar, and ball milled in a ball mill. After the ball milled mixture was taken out, it was centrifuged to wash and remove impurities, and then the centrifuged mixture was freeze-dried to obtain aluminum-doped modified copper oxide nanoparticle catalyst powder; 1.5 g of copper oxide nanoparticle powder, 1 g of gallium salt and 1.5 g of urea are put into a ball milling jar, and ball milled in a ball mill. After the ball milled mixture is taken out, it is centrifuged and washed to remove impurities, and then the centrifuged mixture is freeze-dried to obtain gallium-doped modified copper oxide nanoparticle catalyst powder; 1.5 g of copper oxide nanoparticle powder, 1.2 g of zinc salt, and 1.5 g of urea were put into a ball milling jar, and ball milled in a ball mill. The ball milled mixture was taken out, centrifuged and washed to remove impurities, and then the centrifuged mixture was freeze-dried to obtain zinc-doped modified copper oxide nanoparticle catalyst powder; Step 2: Preparation of gas diffusion electrode of aluminum, gallium and zinc doped modified copper oxide nanoparticle catalyst The aluminum-doped modified copper oxide nanoparticle catalyst and Nafion prepared in step 1 are ultrasonically vibrated in a 2 ml ethanol solution for 30 minutes to prepare an aluminum-doped modified copper oxide nanoparticle catalyst ink, and the catalyst ink is drop-coated on polytetrafluoroethylene hydrophobic carbon fiber paper to prepare a gas diffusion electrode of the aluminum-doped modified copper oxide nanoparticle catalyst; The gallium-doped modified copper oxide nanoparticle catalyst and Nafion prepared in step 1 are ultrasonically vibrated in a 2 ml ethanol solution for 30 minutes to prepare a gallium-doped modified copper oxide nanoparticle catalyst ink, and the catalyst ink is drop-coated on polytetrafluoroethylene hydrophobic carbon fiber paper to prepare a gallium-doped modified copper oxide nanoparticle catalyst gas diffusion electrode; The zinc-doped modified copper oxide nanoparticle catalyst and Nafion prepared in step 1 are ultrasonically vibrated in 2 ml of ethanol solution for 30 minutes to prepare zinc-doped modified copper oxide nanoparticle catalyst ink, and the catalyst ink is drop-coated on polytetrafluoroethylene hydrophobic carbon fiber paper to prepare a gas diffusion electrode of zinc-doped modified copper oxide nanoparticle catalyst; Step 3: Verify the physical properties of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts The physical properties of aluminum-doped modified copper oxide nanoparticle catalyst, gallium-doped modified copper oxide nanoparticle catalyst and zinc-doped modified copper oxide nanoparticle catalyst samples were characterized by X-ray diffraction and scanning electron microscopy respectively. Step 4: Verify the catalytic performance of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts Electron microscope scanning was performed on aluminum-, gallium-, and zinc-doped modified copper oxide nanoparticle catalysts respectively, and the structures of aluminum-doped modified copper oxide nanoparticles, gallium-doped modified copper oxide nanoparticles, and zinc-doped modified copper oxide nanoparticles were analyzed through scanning photos; In a flow cell system, the electrocatalytic carbon dioxide reduction activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified respectively. The gas diffusion electrode loaded with aluminum, gallium, and zinc doped modified copper oxide nanoparticles was used as the cathode, the iridium mesh was used as the anode, the Hg / HgO electrode was used as the reference electrode, and the electrolyte was 1 mol / L KOH; and the catalytic activity of aluminum, gallium, and zinc doped modified copper oxide nanoparticle catalysts was verified by Faraday efficiency diagrams.